The Holocaust - Resnick, Abraham (San Diego, CA Lucent Books, 1991)
Discusses the events surrounding the imprisonment and execution of millions of Jews in Nazi concentration camps during World War II, and the establishment of a Jewish state in Palestine following the war.
Includes bibliographical references (p. 119-122) and index.
Keywords: Holocaust, Jewish (1939-1945) -- Juvenile literature; Holocaust, Jewish (1939-1945)